Formulasi Tablet Ekstrak Daun Kemangi (Ocimum Cannum Sims.) dengan Variasi Konsentrasi CMC-Na Sebagai Bahan Pengikat - Yani Ambari; M. Alwi Rizkillah; Iif Hanifa Nurrosyidah; Dewi Rahmawati; Bella Fevi Aristia (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Basil leaves (Ocimum cannum Sims.) have traditionally been widely used as medicine to cure diseases. Previous research has conducted various studies on the content and efficacy of basil leaves (Ocimum cannum Sims.), so this study aims to innovate by producing tablets. Tablets require various excipients to meet quality requirements. One of them is a binding agent. The purpose of this research is to determine the physical properties of basil leaf extract tablets with different concentrations of CMC-Na binding agent. The binding agent used in this study is CMC-Na with concentrations of 3%, 4%, 5%. Tablet manufacturing is carried out using the wet granulation method, followed by testing the physical properties of the granules including moisture content, flow properties, flow time, compressibility, and testing the physical properties of the tablets including organoleptic evaluation, size uniformity, weight uniformity, hardness test, friability test, and disintegration time test. The evaluation results of the granules showed that F I, F II, and F III met the physical quality requirements except for flow properties and moisture content. The evaluation results of the tablet physical properties showed that all physical properties met the requirements except for hardness, which did not meet the requirements because there were still fines present in the granules during tablet compression. The conclusion of this research is that the hardness test of the tablet did not meet the requirements in all formulas, while size uniformity, weight uniformity, friability test, and disintegration time test met the quality requirements. These results indicate that the different concentrations of CMC-Na in each formula do not affect the physical properties of the tablet Keywords: Binding agent, CMC-Na, Basil leaves, Extract, Tablet